Israel : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Israel was mildly affected by the global recession: following a slowdown in 2009, output is projected to grow by some 4 percent in 2010, led by consumption and exports. Robust fundamentals-including sustained pre-crisis fiscal consolidation-and a swift monetary and fiscal policy response to the external downturn allowed Israel to pass through the global recession relatively unscathed. The resilience of the economy has been strengthened by the adoption of new fiscal rules capping spending and deficits.